The robotic production of spatiality: Predictability, partitioning, and connection - Sumartojo, Shanti; Lundberg, Robert; Kulić, Dana; Tian, Leimin; Carreno‐Medrano, Pamela; Mintrom, Michael; Lugli, Daniele; Allen, Aimee (Transactions - Institute of British Geographers (1965), 2023)
Robots are an increasing presence in our public spaces. Accordingly, in this paper, we make an argument for the importance of understanding how they produce spatiality by developing three robotic logics: predictability, partitioning, and connection. We show how the robotic bias towards orderly categories exists alongside processual accounts of spatiality, and how the forms of anticipatory knowability that robots require play out in the contingent flow of everyday human life, where knowledge emerges as we move in and become engaged with our environments. We analyse the tensions at play here, reviewing how robotic programming and behaviours treat the spaces in which robots operate, and then interrogating robotic ways of understanding, structuring, and acting in their surroundings. This paper argues that, through the emplaced bodies of robots, their computational logics participate in an emergent production of spatiality that always exceeds their preference for knowability. Given that robots are already beginning to reconfigure our cities, we argue that unreflective accommodations of these logics should be resisted, and that we instead need better understandings of how robots' logics shape their agential capacities in our shared worlds.